The effects of tualang honey on nociceptive responses in the thalamus of prenatally stressed male rats offspring - Hasim, Hidani (2018)
Various mechanisms have been postulated to contribute to alteration of nociceptive responses in offspring exposed to prenatal stress; however not a single study has investigated the possible role of thalamus in the nociceptive modulation. The first aim of this study was to investigate the effects of prenatal stress on nociceptive behaviour, morphological changes, level of oxidative stress parameters and NMDA receptors in the thalamus of prenatally stressed male rats offspring. The second aim was to determine the effects of Tualang honey on these parameters. Thirty-three Sprague Dawley pregnant rats were randomised into control, stress and stress-treated with Tualang honey groups. Oral administration of Tualang honey (1.2g/kg body weight/day) or distilled water was given to the corresponding pregnant dams. Restraint stress was applied to the stress and stress-treated groups from day 11 of pregnancy until delivery. Maternal faeces were collected (on day 11 and 21) to measure the level of corticosterone. After parturition, male rats offspring were subjected for nociceptive behavioural testing (n=7 per group). In formalin test, their nociceptive behavior score was recorded. The rats were sacrificed two hours post formalin injection. After that, thalamus of the male rats offspring was removed to determine the level of oxidative stress parameters and NMDA receptors while Nissl staining was performed to detect the morphological changes in the thalamus. All data were analysed by using SPSS, version 22. Nociceptive behaviour score was analysedby using repeated measures analysis of variance (ANOVA) with Bonferroni correction and the remaining data were analysed by using one-way ANOVA. The results of this study demonstrated a significant decrease in nociceptive behaviour score (P<0.05), lower malondialdehyde level with higher catalase, superoxide dismutase activities (P<0.05) and glutathione (P<0.001) in stress-treated with Tualang honey group compared to stress group. Histological observations demonstrated a significant (P<0.05) reduction of Nissl-positive neurons in the left ventral posterolateral thalamic nuclei of the stress group compared to other groups. From this study, it can be concluded that prenatal stress was associated with alteration in nociceptive behavior, oxidative stress parameters, morphology and level of NMDA receptors in the thalamus of adult rats offspring. In addition, Tualang honey administration was associated with improvement in nociceptive behaviour, oxidative stress parameters and morphology in the thalamus of male rats offspring. However, Tualang honey administration did not significantly reduce the NMDA receptors level. The present study provides new knowledge regarding possible mechanisms of antioxidant property of Tualang honey in modulating the nociceptive responses in the thalamus of prenatally stressed male rats offspring.